Pemberdayaan Masyarakat Lokal dalam Pembangunan Pariwisata Berkelanjutan di Tana Toraja, Sulawesi Selatan - Suparjo; Adhi Dana, Yoga; Mahda Kumala, Charisha; Sri Sunarsih, Endang (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2024)
In the Effort to Develop the Tourism Industry in Tana Toraja, with the concept of sustainable development requires the involvement and empowerment of local communities. Local communities have a central role in preserving culture and the natural environment, and are the main beneficiaries of tourism activities. The purpose of this paper is to encourage local communities to actively participate in planning, decision-making, and tourism management processes in their area. Local communities have traditional wisdom in managing natural resources, so their involvement can help ensure that tourism development does not damage the natural environment and local ecosystems. Therefore, empowering local communities is very important in the development of sustainable tourism in Tana Toraja, because it ensures a balance between economic, socio-cultural, and environmental aspects. The method/approach/strategy of community service research uses Participatory Action Research (PAR) an approach that involves active community participation in the entire research process, from problem identification, planning, implementation, to evaluation. The result of this research is the Local Community Empowerment Strategy in Industrial Development in Tana Toraja.